Electronic evidence in criminal proceedings: problematic issues of theory and practice - T. H. Fomina; O. O. Rachynskyi (Bulletin of Kharkiv National University of Internal Affairs)
The article summarises the scientific developments regarding the concept and essence of electronic evidence and provides the author’s own definition to the concept of “electronic (digital) evidence” in criminal proceedings; examines the regulatory framework for the use of electronic (digital) evidence in criminal proceedings; analyses the investigative and judicial practice and the practice of the Supreme Court regarding the admissibility of such evidence in criminal proceedings.